The meaning of company accounts - Reid, Walter; Myddelton, D. R. (David Roderic) (Routledge, 2020)
This title was first published in 2000: The authors' workbook approach provides a treatment of financial accounting practice which readers at differing levels of knowledge can tailor individually to their learning requirements. There is an appendix of photocopiable formats including financial rations and segment analysis.